ANALISIS STRATEGI POLITIK DPD PARTAI GOLKAR DALAM MEMBANGUN CITRA PARTAI (STUDI KASUS DI KABUPATEN ACEH UTARA TAHUN 2024) - Tjasykar, Muhammad; Faraidiany, Maghfira (Journal of Political Sphere, 2025)
This study aims to analyze the political strategies employed by the Regional Leadership Council (DPD) of the GOLKAR Party in building the partys image in North Aceh Regency during the 2024 General Election. The research adopts a descriptive qualitative approach, utilizing data collection techniques such as interviews, observation, documentation, and literature review. The findings reveal that GOLKAR's strategies include implementing social programs, strengthening the role of local figures, and conducting political training. However, challenges remain in the limited use of social media and the uneven distribution of campaign activities. The analysis is grounded in Peter Schroders theory of political strategy and Frank Jefkins public relations theory. The study shows that the DPD GOLKAR Party of North Aceh builds its party image by organizing a Political Institute program for the community. Additionally, GOLKAR maximizes its approach through influential local figures, leveraging their personal closeness to the people. This study recommends that the party should not focus its campaign efforts solely on areas where it already has voter support but should expand its campaigns throughout all regions of North Aceh.